Food security in rural Bangladesh: A comparative study of scientific and grassroots perceptions - Shatil, Tanvir; Islam, m. Rezaul (Sage Journals, 2024)
This article was published in Asia- Pacific Journal of Rural Development [©2024 Rights managed by Sage Journals] and the definite version is available at: https://doi.org/10.1177/1018529124123546 The Article's website is at: https://journals.sagepub.com/doi/10.1177/10185291241235469